CLINICAL SPECTRUM AND OUTCOME OF KEROSENE POISONING IN PEDIATRIC AGE GROUP IN SOUTH KASHMIR: A PROSPECTIVE OBSERVATIONAL STUDY - MAJEED, ANDLEEB; BHAT, MOHD ASHRAF; HUSSAIN, MALIK SHAKIR; TALI, SHOWKAT HUSSAIN; SHAGUFTAYOUSUF; HASSAN, ZULEIDAIN; NAJAR, BILAL AHMAD; AHMAD, SHEIKH MUSHTAQ (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to study the clinical profile of kerosene poisoning, its complications and outcome in children in South Kashmir, J and K, India. Methods: This prospective study of children admitted with kerosene poisoning was conducted in a Govt. Medical College Hospital from January 2019 to December 2021. Demographic data, risk factors, clinical features, and the outcome recorded as per predesigned pro forma were analyzed. Results: A total of 199 children were admitted with acute poisoning and 77 (38.6%) had kerosene poisoning. Majority of the patients was male (77%) in the age group of 1 year–3 years (80.5%) and from an urban background (80.5%). Clinical features mainly included cough (75.3%), vomiting (64.9%), and fever (50.6%). X-ray was showing right lower lobe pneumonia in 23.3% followed by bilateral peri-hilar infiltration (18.1%). The most common risk factors include improper storage and lack of knowledge in family. Conclusion: Kerosene poisoning is a common acute poisoning in pediatric age group. Male children in the age group of 1–3 years are most commonly affected. Improper storage is the most common reason for the accidental poisoning.